Development and Evaluation of a Web-Based MSME Information System for Operational Efficiency and Market Access - Riska Kherani; Vivek Garg; Putri Handayani H; Cut Ita Erliana (Ceddi Journal of Information System and Technology (JST), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in regional economic development, but most MSMEs still face challenges in managing business information, promoting products, and providing customer service that is not yet digitally integrated. This study aims to develop and evaluate a web-based MSME information system to support operational efficiency and market access for MSMEs in Sidenreng Rappang Regency. The study uses a Research and Development approach with a Waterfall model, including the stages of needs analysis, system design, implementation, testing, and maintenance. System evaluation is conducted through functional testing using the black-box testing method and user perception evaluation using a 5-point Likert-scale questionnaire. The research respondents were 30 users, consisting of MSMEs and the general public, who are potential users of the system. The research instrument covers five assessment dimensions, namely ease of use, information quality, interface display, service speed, and digital marketing support. The results of the black-box test indicate that all main features of the system function with 100% success. The results of the instrument reliability test show a Cronbach's alpha of 0.892, indicating good reliability. The results of the quantitative analysis show that the overall average user perception score is 4.36 on a scale of 5.00, which falls in the very good category. In detail, the ease of use dimension obtained a score of 4.41, information quality 4.39, interface display 4.31, service speed 4.22, and digital marketing support 4.47. The results of the study indicate that the developed system is feasible to use and can support operational efficiency and expand market access for MSMEs. The contribution of this study is a development and evaluation model for a web-based MSME information system that can serve as a reference for regional MSME digitalisation programs.